Wamel dalam Tradisi Sewa Menyewa Perspektif Maqashid Al-Shari'ah Studi terhadap Praktek Sewa Sengon di Kecamatan Kedungjajang Lumajang) - Hoirul Ichfan; Nurhafid Ishari (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
This research will discuss about wamel practice in traditional lease perspective maqashid syariah with the aim to describe how wamel practice in kedungjajang sub-district is in accordance with maqashid syariah or not. This study uses a qualitative approach because this research will understand the social phenomena about Wamel in Sub District Kedungjajang District Lumajang. How to collect data through two stages of interview and observation. The data in this research consists of two parts, namely, primary and secondary data. From result of research indicate that: In this wamel maqāṣid Perspective still can’t be in accordance with Maqashid Shariah, that is from the aspect of justice and the benefit of all mankind. Wamel in this Lease traditions sengon in it contain benefits or benefits achieved but with harmful also caused.